PENGARUH LATIHAN PEREGANGAN PERUT TERHADAP NYERI MENSTRUASI (Politeknik Kesehatan Kemenkes Bandung, 2022)
The impact of menstrual disorders on adolescent girls include disturbances, activity disturbances, sleep patterns, appetite disorders, interpersonal relationships, when concentrating on work and study. Pain also affects the emotional state of the feeling realm. Adolescents who experience dysmenorrhea when limiting their daily activities, especially learning activities at school. This study was to determine the effect of Abdominal Stretching Exercises on Menstrual Pain. Evidence-Based Case Reports (EBCR). Aims to determine the effect of Abdominal Stretching Exercises on Menstrual Pain/Dysmenorrhea. Two articles were obtained by searching articles through the Garuda Portal and Google Scholar with a quasi-experimental design with one group pretest posttest by Murtiningsih, et al and Faridah, et al. Abdominal stretching exercise is an effective non-pharmacological therapy used in reducing menstrual pain because the movement is easy and safe because it uses the body's physiological functions and does not require tools in its implementation.